The evaluation of drought-tolerance rice genetic resources - Theophilus Amar-Cofie Quashie; Eric Yerenkyi Danquah (International Journal on Food, Agriculture and Natural Resources, 2022)
About 70% of the rice consumed in Ghana is imported. The state of self-insufficiency in rice production can be attributed to the lack of adequate or continuous water supply. Rice, being an aquatic plant, is not tolerant to drought, which is known as the most threatening abiotic factor causing as much as 64% yield reduction. Therefore, this study was conducted to identify drought-tolerance genotypes among 24 rice collections and to estimate their heritability. A total of 24 traits were assessed in this study, and three treatments were applied, including stress free, mild stress, and severe stress, each of which involved three replications. The results showed that most of the parameters under investigation, including panicle length, fertile panicle rate, shoot, and root dry weight, and maximum root depth, decreased considerably as the level of drought stress increased. In addition, five of the accessions showed considerable tolerance to drought, eight accessions were high yielding, and eight accessions combined high yields and drought tolerance. The study concluded that 80% of the rice accessions offer promising lines to be used as parents in the development of drought-tolerant varieties and in genetic improvement programs aimed at such a purpose. The study recommended that molecular studies and morphological characterization should be done on the collections to understand their genetic makeup, similarities, and differences.